Dvarashakha of the central shrine among the Triple-shrine Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the dvarashakha (architrave) of the central shrine among the Triple-shrine Temple. Compared to the identical shrines flanking it, the dvarashakha of this shrine has minimal ornamentation. The vertical divisions of the dvarashakha are plain except for the lower portion called the udumbara which has attendants carved inside niches with toranas (decorative archways or gateways). The lintel beam had a depiction of three goddesses and the threshold. From left to right, the three goddesses on the lintel are Bramhani, Maheshvari, and Vaishnavi.